The central polynomials for the finite dimensional Grassmann algebras - Koshlukov, P.; Krasilnikov, A.; Elida Alves da Silva (Algebra and Discrete Mathematics, 2009)
In this note we describe the central polynomials for the finite dimensional unitary Grassmann algebras Gk over an infinite field F of characteristic ≠2. We exhibit a set of generators of C(Gk), the T-space of the central polynomials of Gk in a free associative F-algebra.